Aqidah Education in the Perspective of Developmental Psychology : Case Study of Student in Kajen Hamlet, Giri Village, Kebomas District, Gresik Regency, East Java - Rafiqah Dwi Rahmah (Insight School Academy, 2023)
Introduction to the Problem: Life in today's era is increasingly undergoing changes – changes that are very significant and so fast. Religious styles also undergo changes, of course, will have an impact on the value of religion itself. The importance of religious education in this global era to fortify society from the negative effects of globalization. As an effort made can be through Aqidah education. Purpose: This article aims to discuss the understanding of Aqidah education for children today and Aqidah education in the perspective of developmental psychology. Design/method/approach: this research is a qualitative research case study that is described critically. Data collection techniques with semi-structured interviews by making interview guidelines as an outline. Analyzing data using triangulation techniques so as to make the results of this study richer with treasures in it. This technique can also be used to test the credibility of data. Findings: The results of this study state that the understanding of Aqidah education from the four female students has a tiered level of understanding. In the perspective of developmental psychology by analyzing existing theories there are conditions for different understandings of Aqidah education according to age, intellectual improvement, religious interests, family background and living environment. Implications/Limitations of Research: This study provides suggestions for future researchers to increase the number of respondents interviewed, especially to male students. Originality/value: This study found an important finding that the higher the level of education and age, the more understanding and aware of the importance of understanding Aqidah correctly.